(untitled) (Journal of Parents and Teachers, 2015)
Most of the iconography of leadership shows a man with a firm aspect, indicating the path to his supporters who walk following him. This image has evolved in the last decades, mainly since women integrated in the leadership of organizations, and their emotional involvement to their own leaderships. Subordinate followers from the previous period are transformed now into co-workers of a common project. Leadership is distributed having in mind the capacities of each member of the team and implication, compromise, and empathy are the fundamental ingredients of a team work in which the strategic plan, the risks, achievements and collaborative results are shared. These have been the components taken into account when presenting a new style of positive and shared leadership, able to implicate collaborators in a suggestive and potential project. We consider collaborator everyone in the school able to have a clear influence upon those they have to supervise, that is to say, the people in directive jobs, teachers in their teaching, and in the coordination structures, families who participate in the Educative Project of the school, and first line workers, very important to make possible the running of the organization.